Ligand Substitution of Ru(II)–Alkylidenes to Ru(bpy)(3) (2+): Sequential Olefin Metathesis/Photoredox Catalysis - Gallhof, Malte (Chemistry, 2020)
Ruthenium(II) alkylidene complexes such as the Grubbs’ 1st and 2nd generation catalysts undergo a ligand substitution with 2,2′‐bipyridine, which readily leads to the common photoredox catalyst Ru(bpy)(3) (2+). The application of this catalyst transformation in sequential olefin metathesis/photoredox catalysis is demonstrated by way of ring‐closing metathesis (RCM)/photoredox ATRA reactions.